THAIFUR ALI WAFA AL-MADURI AND COUNTER-NARRATIVE OF MUKTAZILAH IN FIRDAWS AL-NAÊ¿ÄªM BI AL-TAWá¸ŒÄªá¸¤ MAÊ¿Ä€NÄª Ä€YÄ€T AL-QUR'Ä€N AL-KARÄªM - Atfal, Khairul; Zaidanil Kamil, Ahmad; Bakar, Abu (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
This article discusses Thaifur Ali Wafa's response to the polemics of Islamic theology in Madura through his monumental work Tafsir Firdaws al-NaÊ¿Ä«m. As a pesantren cleric and structural NU figure, Thaifur represents Madurese clerical authority. In his career, he provides critical responses to Muktazilah thoughts, including such issues as the inability to see God in heaven, God's obligation to do good, and God's promises and threats. This library research uses the content analysis method. Using the sociology of knowledge approach, this study finds that Thaifur Ali Wafa's response to Muktazilah thought reflects the strong influence of Ahl al-Sunnah wa al-Jama'ah ideology. This ideology was formed due to Madurese cultural factors and Thaifur Ali Wafa's scientific genealogy. This article is significant in illustrating the network and intellectual relationship between Nusantara Muslims and Middle Eastern scholars, which is crucial in the writing of Islamic scholarly works in the archipelago, including in Madura. It reflects the complexity and diversity of Islamic thought in the region, which is influenced by intercultural interactions and intellectual exchanges that have taken place over centuries.